2016
DOI: 10.1108/nfs-08-2015-0091
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality of commonly consumed street foods in Bangladesh

Abstract: Purpose – The purpose of this review is to narrate the microbiological quality of variety of street foods which are largely consumed by the Bangladeshi people of all ages. However, these foods are prone to microbial contamination. Most of the vendors lack the awareness on hygiene during preparing, processing or handling the foods. The insufficiency in regular microbiological analysis further casts the possibility of disease onset. The need of microbial analyses of these foods also remains uncle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 55 publications
0
24
1
Order By: Relevance
“…The bacteria can cause different types of food borne disease both by causing infection and intoxication (29). The environmental condition during transport and storage also encouraged the bacteria to multiply rapidly.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The bacteria can cause different types of food borne disease both by causing infection and intoxication (29). The environmental condition during transport and storage also encouraged the bacteria to multiply rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…While eating raw, we often consume fruits along with such pathogenic and drug resistant microorganisms if not washed properly (28,29). Different types of infectious diseases can arise from consuming the contaminated fruits.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…globe, Bangladeshi people are more likely to be prone to microbial attack due to the relatively dense population with extremely unhygienic sanitary facilities (11,31,32). Several researches revealed that the propagation of waterborne microorganisms into the environment causing cholera and diarrhoea is very frequent in this country (32)(33)(34).…”
Section: Microbiological State Of Common Foods In Bangladeshmentioning
confidence: 99%
“…In principle, the microbial load of plants is the result of a series of influences caused by animate & inanimate sources and microbial contaminates are easily transferred via air and soil borne vectors (20)(21)(22)(23). Furthermore, original microflora in plants, presence of microorganisms within processing plant, dust, using contaminated water and animal human a excreta, before and after harvest procedure including processing, storage and distribution may be the origins of microbial contamination (20,24).…”
mentioning
confidence: 99%